Creating order and stability? The Dairy Marketing Board, milk (over)production and the politics of marketing in colonial Zimbabwe, 1952-1970s (Historia, 2021)
his article examines the efforts of the Dairy Marketing Board (DMB) in stabilising the dairy industry in the wake of difficulties that emerged in the production and marketing of dairy products after World War Two. It traces and evaluates the marketing and distribution strategies the DMB used, and their strengths and weaknesses. It illustrates the point that while shortages which had characterised war-time and post-war Southern Rhodesia had been eliminated by the mid 1950s, continued increased production led to over production which in turn created serious challenges for the Board in finding markets for the lucrative liquid milk trade. This article analyses the general national policy of self sufficiency in agricultural production that was espoused during the course of the war and were pursued vigorously after the war. It argues that this policy was not feasible for the dairy sector because it proved cheaper to import cheese and skimmed milk powder than to produce it locally. It is also maintains that while the voluntary takeover and recapitalisation of struggling private concerns on the distribution side was necessary in the 1950s, the employment of legislative instruments to elbow private concerns out of the milk market from the 1960s onwards was not in the best interests of the industry. Instead, these tactics were aimed at placating the DMB financially - a move that was unfair to both private players and consumers.  Hierdie artikel ondersoek die pogings van die Suiwel Bemarkingsraad (Dairy Marketing Board [DMB]) om, in die lig van die produksie en bemarkings probleme wat in die vaarwater van die Tweede Wêreldoorlog ervaar is, die suiwelbedryf te stabiliseer. Dit ondersoek en evalueer die sterk en swakpunte van die bemarkings en verspreidings strategieë wat die Raad gebruik het. Die artikel argumenteer dat hoewel die tekorte wat tydens en direk na die oorlog in Suid-Rhodesië ondervind is teen die middel vyftigerjare uitgeskakel is, die voortgesette toename in produksie tot oorproduksie gelei het. Hierdie oorproduksie het die Raad genoodsaak om nuwe markte vir die winsgewende handel in vloeibare melk te vind. Hierdie studie analiseer die algemene nasionale beleid van selfvoorsienendheid ten opsigte van landbouproduksie wat tydens die oorlog beslag gekry het en na die oorlog doelgerig nagestreef is. Die referaat argumenteer dat die beleid in die lig van die beskikbaarheid van goedkoper ingevoerde kaas en afgeroomde poeiermelk, nie vir die suiwelbedryf haalbaar was nie. Dit word ook geargumenteer dat terwyl die vrywillige oorname en die herkapitalisering van sukkelende privaat verspreiders van suiwelprodukte noodsaaklik was in die 1950's, die aanwending van wetgewing in die 1960's om privaat produsente uit die melkmark te dryf nie in die bedryf se beste belang was nie. Die taktiek wat daarop gemik was om die Raad finansieel ter wille te wees was onregverdig teenoor beide die privaat rolspelers as die verbruikers.
Keywords: Produsent-kleinhandelaars; Suiwel bemarkingraad; Producer-retailers; Dairy Marketing Board